Potential and limitations of ozone in marine recirculating aquaculture systems - Guidelines and thresholds for a safe application - Schröder, Jan (2011)
The aim of the present thesis was to assess the potential and limitations of ozonation in marine recirculating aquaculture systems (RAS) while particularly focussing on the toxicity, formation and removal of ozone-produced oxidants (OPO) in order to develop guidelines and thresholds for a reasonable and safe ozone application. In the first two chapters the toxicity of OPO was investigated for Pacific white shrimp (Litopenaeus vannamei) and turbot (Psetta maxima) and maximum safe exposure levels were determined for both species. Despite their strong differences in biology, both investigated species possess a similar sensitivity towards OPO. Results demonstrate that OPO concentrations ≥ 0.10 mg/l cause adverse effects in both species. An OPO concentration of 0.06 mg/l was determined as the maximum safe exposure level for rearing juvenile L. vannamei and P. maxima. Furthermore, we proved this safe level to be sufficient to control and reduce bacterial biomass in the recirculating process water. To improve the control of toxic OPO, the removal performance of activated carbon filtration was tested for different oxidant species (free bromine, bromamines, free chlorine and chloramines). Results proved activated carbon filtration to be very efficient in removing the dominating oxidant species free bromine and bromamines formed during the ozonation of natural and most artificial seawaters. In contrast, removability of chloramines, sometimes present in ozonated bromide-free artificial seawater, was shown to be significantly lower. Finally the suitability of ozone for water quality improvement was evaluated by investigating the ozone-based removal of nitrite, ammonia, yellow substances and total bacterial biomass with regard to feasibility, efficiency as well as safety for the cultivated organisms. Results demonstrate that ozone can be efficiently utilized to simultaneously remove nitrite and yellow substances from process water in RAS without risking the formation of toxic OPO concentrations. Although ammonia oxidation in ...